Advances in Neuroergonomics and Cognitive Engineering : Proceedings of the AHFE 2019 International Conference on Neuroergonomics and Cognitive Engineering, and the AHFE International Conference on Industrial Cognitive Ergonomics and Engineering Psychology, July 24-28, 2019, Washington D. C., USA. /: Proceedings of the AHFE 2019 International Conference on Neuroergonomics and Cognitive Engineering, and the AHFE International Conference on Industrial Cognitive Ergonomics and Engineering Psychology, July 24-28, 2019, Washington D. C., USA. ([2019]) - Unknown
No abstract available